2014
DOI: 10.1007/s13277-014-2683-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical role of NF45 as a novel cell cycle protein in esophageal squamous cell carcinoma (ESCC)

Abstract: NF45 (also known as ILF2), as one subunit of NF-AT (nuclear factor of activated T cells), repairs DNA breaks, inhibits viral replication, and also functions as a negative regulator in the microRNA processing pathway in combination with NF90. Recently, it was found that implicated in the mitotic control of HeLa cells and deletion of endogenous NF45 decreases growth of HeLa cells. While the role of NF45 in cancer biology remains under debate. In this study, we analyzed the expression and clinical significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…Therefore, NF45 may possess oncogenic property in the development of various cancer types. Furthermore, a recent report identified a close correlation between NF45 expression and tumor stage in esophageal squamous cell carcinoma (ESCC) and that NF45 was an independent prognostic factor for ESCC patients' poor survival [13]. In keeping with these findings, we found that NF45 expression was significantly associated with tumor size (p = 0.007), histological differentiation (p = 0.033), and TNM stage (p = 0.001).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Therefore, NF45 may possess oncogenic property in the development of various cancer types. Furthermore, a recent report identified a close correlation between NF45 expression and tumor stage in esophageal squamous cell carcinoma (ESCC) and that NF45 was an independent prognostic factor for ESCC patients' poor survival [13]. In keeping with these findings, we found that NF45 expression was significantly associated with tumor size (p = 0.007), histological differentiation (p = 0.033), and TNM stage (p = 0.001).…”
Section: Discussionsupporting
confidence: 87%
“…In agreement with the data, we showed that high NF45 expression was observed in pancreatic ductal adenocarcinoma, whereas low expression was noted in normal pancreas. In addition to pancreatic cancer, NF45 has been reported to be overexpressed in glioma, cervical cancer, and esophageal cancer [11][12][13]. Therefore, NF45 may possess oncogenic property in the development of various cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other studies have reported higher expression of hnRNP‐B1 (Matsuyama et al, ) and ‐H1 (Sun, Liu, Liu, & Zhao, ), NF45 (Ni et al, ), insulin‐like growth factor 2 mRNA‐binding protein (IGF2BP)‐2 (Barghash, Golob‐Schwarzl, Helms, Haybaeck, & Kessler, ) and ‐3 (W. Feng et al, ; Kazeminezhad, Mirafsharieh, Dinyari, Azizi, & Ebrahimi, ; Trivedi, Cartun, & Ligato, ), DEAD‐Box Helicase 46 (B. Li, Li, et al, ), and Musashi‐1 (Mokrowiecka et al, ) in EC tissues. Because enhanced expression of these molecules was correlated with poor pathologic features and worse survival of patients, they are thought to be useful as new prognostic markers and potential anticancer targets in EC.…”
Section: Major Functions Of Rbps In Gi Cancermentioning
confidence: 97%
“…ILF2 is ubiquitously expressed in human tissues, especially the brain, thymus, pancreas, kidney and testis indicating that it is involved in the physiology of various cell types (4). ILF2 has been reported to promote the progression of multiple cancer types including cervical cancer, esophageal squamous cell carcinoma, glioma, pancreatic carcinoma and non-small cell lung cancer (58). Yet, the regulatory mechanisms of ILF2 remain largely elusive.…”
Section: Introductionmentioning
confidence: 99%